N‐ and O‐linked glycosylation site profiling of the human basic salivary proline‐rich protein 3M. Issue 10 (29th April 2016) - Manconi, Barbara; Cabras, Tiziana; Sanna, Monica; Piras, Valentina; Liori, Barbara; Pisano, Elisabetta; Iavarone, Federica; Vincenzoni, Federica; Cordaro, Massimo; Faa, Gavino; Castagnola, Massimo; Messana, Irene
Abstract : In the present study, we show that the heterogeneous mixture of glycoforms of the basic salivary proline‐rich protein 3M, encoded by PRB3‐M locus, is a major component of the acidic soluble fraction of human whole saliva in the first years of life. Reversed‐phase high‐performance liquid chromatography with high‐resolution electrospray ionization mass spectrometry analysis of the intact proteoforms before and after N‐deglycosylation with Peptide‐N‐Glycosidase F and tandem mass spectrometry sequencing of peptides obtained after Endoproteinase GluC digestion allowed the structural characterization of the peptide backbone and identification of N‐ and O‐glycosylation sites. The heterogeneous mixture of the proteoforms derives from the combination of 8 different neutral and sialylated glycans O‐linked to Threonine 50, and 33 different glycans N‐linked to Asparagine residues at positions 66, 87, 108, 129, 150, 171, 192, and 213.